The Relationship of Personal Hygiene Knowledge in the Incidence of Vaginal Discharge A Systematic Review of Cross-Sectional Studies - Mentari Rizqoh Eka Pratiwi; Prio Sasmito; Marwan TP Kase (Yayasan Adra Karima Hubbi, 2023)
Genital hygiene is an important part of a woman's health and important for protecting reproductive health. Women engage in many genital hygiene practices that have direct and indirect effects on the genitals and the potential for sexually transmitted infections. Every year, around 100 million women worldwide are affected by genital infections which can cause vaginitis, cervicitis, and urethritis, and trichomoniasis (Shah et al., 2019). Young women alone already have an estimated incidence of vaginitis of 10-25% (Tavani et al., 2015). This systematic literature review aims to present a systematic review of the relationship between personal hygiene in maintaining vulvar hygiene and leucorrhoea. The population is women of various age ranges. To present a systematic review of cross-sectinal approaches with 8 journals from 2016 to 2022. The results of the study (Prasanthi et al., 2017) for knowledge about vaginal discharge, 98.5% obtained <50% and only 8 (1.5% ) which has a score between 50% -75%. The conclusion of various cross-sectional studies has provided evidence that there is a lack of knowledge about personal hygiene for vaginal discharge among women of childbearing age. The findings of this study provide an insight that knowledge of personal hygiene on vaginal discharge in the productive age group must be increased and as health workers provide more information or education to women about vaginal discharge to improve their quality of life.